WEB-BASED AUDIOVISUAL NUTRITION EDUCATION VIA WHATSAPP FOR ADOLESCENTS: A PRE-EXPERIMENTAL STUDY - Amita, Dzikra Fitria; Muslim, Muhammad Panji (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Adolescence is a critical period that plays an essential role in fulfilling nutritional needs. Inadequate nutrient intake during this phase can hinder physical growth and cause mental developmental disorders. One effort to improve nutritional knowledge is through technology-based edutainment, such as the use of Android applications and websites. Audiovisual educational media delivered via WhatsApp provides an effective interactive platform to enhance adolescents’ knowledge, attitudes, and behaviors regarding balanced nutrition. This study aimed to evaluate the effectiveness of website-based audiovisual media delivered through WhatsApp in improving nutritional knowledge and attitudes among 11 students at SMP Darul Qur’an Padang, with inclusion criteria: (1) had never received health education, (2) were active students, (3) were willing to participate in the intervention, (4) owned a personal smartphone, and (5) had WhatsApp installed and accessible for video calls. Data were collected using pretest and posttest questionnaires. The results showed a significant improvement in both knowledge and nutritional attitudes after the intervention (p-value = 0.000). The average knowledge score increased from 11.55 (pretest) to 17.09 (posttest), while the average attitude score increased from 40.09 to 44.36. Based on these findings, future studies are recommended to expand educational media by incorporating interactive features (such as educational games or online discussion forums) to further enhance student engagement